Forecasting the future drought in Bukit Merah using HECHMS software - Malik, Alia Farhana; Hamidon, Nuramidah; Adly Fitry, Nurul Izzah; Mohd Arish, Nur Aini; Awang, Mariah; Abd Rahman, Muhammad Ashraf; Murugan, Dharshilan; Abdullah, Nor Maizzaty (2024)
Drought is a worldwide phenomenon caused by irregular rainfall patterns and rising temperatures. Malaysia, such as in Bukit Merah, has experienced floods and droughts due to climate change. Therefore, the objectives of this study were to calibrate and validate the rainfall-runoff of Bukit Merah and determine the future drought in HEC-HMS simulation. The Hydrologic Engineering Centre – Hydrologic Modelling System (HEC-HMS) is designed to simulate the rainfallrunoff of the basin. The study area's daily rainfall (mm) data were obtained from the Department of Irrigation and Drainage (DID) from 2010 to 2019. One rainfall streamflow station was the station was used in this study area. Previous data performed the different data from the hydrologic model of Bukit Merah for calibration and validation with the coefficient of R2 = 0.708 and 0.574, respectively. The model was used to simulate the drought for the next thirty years (2020 – 2050) using SDSM's forecasted rainfall data. The modelling predicts over 30 years the lowest peak discharge is 1.06 m3/s (01 Jan 2020; 00:00), 2.13 m3/s (18 Feb 2021; 00:00), 1.98 m3/s (24 Jan 2025; 00:00), 2.47 m3/s (12 Mar 2025; 00:00) and 2.94 m3/s (14 Feb 2049; 00:00). Therefore, the drought forecasting was done using the hydrologic model, HEC-HMS, as disaster prevention. The HEC-HMS will forecast the streamflow magnitude and date, allowing the government to plan ahead of time towards drought disaster. Also recommended is the continuous recording of rainfall and runoff data, recorded at intervals that correspond to one another in time. Install automatic recording stations for streamflow and rainfall at each river exit and ensure that these recording stations are kept in good working order at all times